2017
DOI: 10.1097/mpg.0000000000001532
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Incidence and Altered Presentation in a Population‐based Study of Pediatric Celiac Disease in North America

Abstract: Background Celiac disease (CD) is a common immune-mediated disorder that affects up to 1% of the general population. Recent reports suggest that the incidence of CD has reached a plateau in many countries. We aim to study the incidence and altered presentation of childhood CD in a well-defined population. Methods Using the Rochester Epidemiology Project, we retrospectively reviewed Mayo Clinic and Olmsted Medical Center medical records from January 1994 to December 2014. We identified all CD cases of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 42 publications
7
54
1
Order By: Relevance
“…The proportion of monosymptomatic to polysymptomatic clinical presentation is in agreement with recent studies that showed an altered clinical picture in the United States and the Netherlands in recent decades [26,27].…”
Section: Discussionsupporting
confidence: 79%
“…The proportion of monosymptomatic to polysymptomatic clinical presentation is in agreement with recent studies that showed an altered clinical picture in the United States and the Netherlands in recent decades [26,27].…”
Section: Discussionsupporting
confidence: 79%
“…13,14 The inclusion criteria were the following: (1) positive serology markers, such as antitissue transglutaminase immune globulin A; (2) confirmatory small bowel biopsy specimen that showed the characteristic histologic findings (increased intraepithelial lymphocytes, villous atrophy, and crypts hyperplasia); (3) Olmsted County residents at the time of index date (Olmsted County residency was established by the residency at the time of diagnosis); and (4) research authorization for using medical records for research. Exclusion criteria were the following: (1) non-Olmsted County residency at the time of diagnosis; (2) no research authorization for use of medical records for research; (3) patients without confirmatory small bowel biopsy for CD; and (4) other diseases that cause villous atrophy, including autoimmune enteropathy, inflammatory bowel disease, and small bowel bacterial overgrowth.…”
Section: Case Ascertainmentmentioning
confidence: 99%
“…This study was approved by the institutional review board at Mayo Clinic and Olmsted Medical Center. In this study, we identified and enrolled eligible children with CD (cases) between 1997 and 2014 who resided in Olmsted County, Minnesota, 13 and these cases were then matched by birth year and sex to obtain their corresponding control subjects. We then compared the frequency of a history of asthma between patients in the cases and the controls.…”
Section: Study Design and Subjectsmentioning
confidence: 99%
“…Irrespective of the presence of a positive serology, intestinal histopathological analysis is still considered a determinant requirement for FPIGD diagnosis . The most serious lesions usually occur in the proximal small intestine and tend to diminish in severity as they approach the large intestine . In the classification system proposed by Marsh, the subclinical stages of FPIGD were classified as Phase 1 (infiltrative type) and Phase 2 (hyperplastic type), while the stage where clinical signs and symptoms are present, Phase 3 (destructive type), was frequently observed.…”
Section: Discussionmentioning
confidence: 99%
“…13,26 The most serious lesions usually occur in the proximal small intestine and tend to diminish in severity as they approach the large intestine. 27 In the classification system proposed by Marsh, 24 the subclinical stages of FPIGD were classified as Phase 1 (infiltrative type) and Phase 2 (hyperplastic type), while the stage where clinical signs and symptoms are present, Phase 3 (destructive type), was frequently observed. Later, Oberhuber 14,25 proposed a subdivision of Phase 3 into 3a, 3b and 3c, characterized by increasing damage to the mucosa.…”
Section: Discussionmentioning
confidence: 99%